LAW ENFORCEMENTS AGAINST ACTS OF TERRORISM ACCORDING TO ARTICLE 6 OF LAW NUMBER 5 OF 2018 - Jhuan Felixs Gultom; Octo Iskandar; Aly Ashghor (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2024)
This research departs from the high crime rate caused by terrorism in the territory of the Republic of Indonesia. Meanwhile, Indonesia is a rule of law which aims to create a just and prosperous society. This research aims to: (1) Find out the elements regulated in Article 6 of Law Number 5 of 2018. (2) Find out the forms of accountability or sanctions for perpetrators of criminal acts of terrorism according to Article 6 of Law Number 5 of 2018. This research using Normative research type. The collection of legal materials is carried out using the Statute Approach and Case Approach techniques. The data sources used are primary, secondary and tertiary data. The results of research and discussions show that ratification of the Terrorism Bill (RUU) is an urgent need, especially considering the increasing threat of terror in the country. The existence of the law can be used by the authorities, one of which is that the police can take direct action against individuals who are proven to be affiliated with the ideology of certain terrorist groups.